Food waste perception of workplace canteen users — a case study - Pires, Iva (2022)
Background: Food waste occurs in all stages of the food supply chain, namely in the food service sector. Understanding how much and why food is wasted and whether consumers are aware of it is essential to design effective interventions in this setting. This case study aims to compare the food waste perception by consumers and measure plate waste in a Portuguese workplace canteen in order to recognize if trained consumers can estimate his/her food waste. Methods: Data were collected from 160 users randomly selected attending a workplace canteen during one month. Plate waste was evaluated by the weighing method. Visual estimation was performed by each participant to evaluate food waste perception at the end of the meal. Consumers were also asked about reasons for wasting food. Results: Plate waste was 8.4% for soup, 9.0% for the main course, and 4.0% for dessert. These values follow the same trend of waste perceived by consumers for soup (R = 0.722; p < 0.001), main course (R = 0.674; p < 0.001), and dessert (R = 0.639; p < 0.001), showing a high relation between self-assessment and measured plate waste. Excessive portions (46.1%), dislike of meal flavor (18.6%), cooking method (8.8%), and texture (3.9%) were identified as the main causes for plate waste. Conclusions: Canteen users showed an accurate perception of their plate waste for all meal components. Excessive portions were identified by consumers as the main reason for plate waste.